Glycaemic control and mortality in older people with type 2 diabetes: The Fremantle Diabetes Study Phase II. Issue 12 (10th August 2018) - Bruce, David G.; Davis, Wendy A.; Davis, Timothy M. E.
Abstract : Aim: To investigate whether tight glycaemic control achieved with metformin, insulin or sulphonylurea‐based pharmacotherapy increases all‐cause mortality in older people with type 2 diabetes. Materials and Methods: We conducted a prospective cohort study of individuals with known diabetes recruited between 2008 and 2011 and followed until 2016. The impact of baseline glycated haemoglobin (HbA1c) on mortality hazards was investigated in participants aged ≥75 years. Proportional hazards models for time to death were constructed from the baseline clinical assessment, then the variables of interest (HbA1c, treatment category and their interactions) were entered. Results: There were 367 participants (mean age 80.1 ± 3.9 years, median [interquartile range] HbA1c 50 [45‐56] mmol/mol or 6.7 [6.3‐7.3]%) who were followed for a median (interquartile range) 6.7 (4.5‐7.7) years, during which 40.9% of the participants died. At baseline, 60.4% were on metformin‐based treatment, 35.3% on sulphonylurea‐based treatment and 23.2% on treatment including insulin. Baseline HbA1c was significantly associated with mortality in a model that included interactions between HbA1c and the three treatment‐based groups compared with non‐pharmacological treatment. The metformin treatment group had higher mortality when HbA1c levels were <48 mmol/mol (<6.5%) and the sulphonylurea and insulin treatment groups had higher mortality when HbA1c levels were <52 mmol/mol (<7.0%), with hazard ratios of 2.63 (95% confidence interval [CI] 1.39‐4.97), 2.49 (95% CI 1.14‐5.44) and 2.22 (95% CI 1.12‐4.43), respectively. Conclusions: Tight glycaemic control may be hazardous in older people with type 2 diabetes when achieved with pharmacotherapy with metformin, and especially with insulin or sulphonylureas. These data confirm that overtreatment is likely to be an important clinical problem in this vulnerable population.